Anxiety and Emotional Intelligence: Comparisons Between Combat Sports, Gender and Levels Using the Trait Meta-Mood Scale and the Inventory of Situations and Anxiety Response - Fernández, María Merino; Brito, Ciro José; Miarka, Bianca; Díaz-de-Durana, Alfonso Lopéz (Frontiers in Psychology, 2020)
The present study compared emotional intelligence and anxiety between six combat sports of lower, intermediate and high-level female and male athletes. The sample was composed by 444 athletes (age: 24.7±8.8 yrs., body mass: 72.4±12.1kg, height: 1.82±0.3m, practice time: 13.1±7.4 yrs.) separated by sex (male n=273, female n=171) from different combat sports (jiu-jitsu n=142, judo n=137, karate n=57, kendo n=63, taekwondo n=25 and freestyle wrestling n=20) of three levels (high-level n=57, intermediate n=137 and low-level n=142). Inventory of situations and anxiety response (ISRA) provided an independent evaluation for the three systems: cognitive, motor and physiological, as well as a total with four factors of analysis (anxiety before the evaluation, interpersonal, phobic and before habitual and daily situations). Trait Meta-Mood Scale (TMMS-24) verified emotional intelligence scales. Descriptive results are demonstrated by percentage or median (Q1; Q3), Kruskal-Wallis and Mann-Whitney tests were conducted to compare groups, p≤0.05. The main results demonstrated 10% more total anxiety for wrestling and judo compared to the other groups (p≤.05). Female athletes showed 15% more anxiety than men, while emotional attention demonstrated 10% better results for women. Significant differences were observed between high- versus low-level athletes in the total anxiety with 85 (44; 143) versus 122 (69; 186) of ISRA index and emotional repair with 30 (25; 34) versus 27 (22; 32) of TMMS-24 index. Emotional intelligence seems to be higher in female and in higher level, while anxiety appears to be prevalent in judo and wrestling, low-level and in female athletes. These outcomes provide support for the hypothesis that emotional abilities are an important contributor to emotional intelligence, particularly differentiating high level athletes than other levels. Results can be incorporated into strategies for reducing anxiety and improving emotional intelligence, considering particularities of gender and level groups.